Blocking HIV‐1 transmission in the female reproductive tract: from microbicide development to exploring local antiviral responses. Issue 10 (9th October 2015) - Eid, Sahar G; Mangan, Niamh E; Hertzog, Paul J; Mak, Johnson
Abstract : The majority of new HIV‐1 infections are transmitted sexually by penetrating the mucosal barrier to infect target cells. The development of microbicides to restrain heterosexual HIV‐1 transmission in the past two decades has proven to be a challenging endeavor. Therefore, better understanding of the tissue environment in the female reproductive tract may assist in the development of the next generation of microbicides to prevent HIV‐1 transmission. In this review, we highlight the important factors involved in the heterosexual transmission of HIV‐1, provide an update on microbicides' clinical trials, and discuss how different delivery platforms and local immunity may empower the development of next generation of microbicide to block HIV‐1 transmission in the female reproductive tract.